HUBUNGAN PROFESIONALISME APARATUR PEMERINTAH DENGAN KUALITAS PELAYANAN PUBLIK - Bonde, Switika (JURNAL ADMINISTRASI PUBLIK, 2013)
Abstrak : Research carried out in the framework of thesis writing as one of the final project to earn a Bachelor's degree or bachelor degree at the Faculty of Social and Political Sciences Unsrat Manado is preceded by preliminary observations indicate that the quality of public services in the District Pineleng still low . This condition seems to be related to the level of professionalism officials also indicated that low. Thus , this study aimed to analyze the relationship between professionalism apparatus with the quality of public services in the district of Minahasa Pineleng . This study uses descriptive quantitative approach. Data were collected through questionnaires spread technique to 40 respondents from the elements and forces 40 people from the community element of service users . Data were analyzed by applying analytical techniques percentage or frequency tables analysis , and to test the hypothesis applied engineering product moment correlation analysis and simple linear regression . The results showed that the distribution of the respondents' answers to all the variables , both independent variables ( the professionalism of civil servants ) and the dependent variable ( quality of public services ) is quite varied , but the average is at medium or medium category . Meanwhile , the condition of public service quality perceived by the respondents are also service users in the category , but relatih not satisfactory . The conclusion of this study is bahawa professionalism of civil servants have a positive and significant relationship with the quality of public services , and related to both the contributive . Means that the increase or decrease in the quality of public services is determined by the professionalism of the officers in the public service task . It is recommended that the District government concern about the increasing professionalism of government officials , particularly at the village and district Pineleng through functional training techniques .Keywords : professionalism , Quality Public Services